1999
DOI: 10.2307/2656933
|View full text |Cite
|
Sign up to set email alerts
|

The cytoplast concept in dividing plant cells: cytoplasmic domains and the evolution of spatially organized cell division

Abstract: The unique cytokinetic apparatus of higher plant cells comprises two cytoskeletal systems: a predictive preprophase band of microtubules (MTs), which defines the future division site, and the phragmoplast, which mediates crosswall formation after mitosis. We review features of plant cell division in an evolutionary context and from the viewpoint that the cell is a domain of cytoplasm (cytoplast) organized around the nucleus by a cytoskeleton consisting of a single "tensegral" unit. The term "tensegrity" is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 156 publications
10
113
0
1
Order By: Relevance
“…Most hydrolyzable polyphenols effectively complex proteins, and thus might inhibit enzymes (Haslam, 1989). The occurrence of hydrolyzable polyphenols in chlorophytes is limited to species belonging to the 'phragmoplast' group (see Sawitzky and Grolig, 1995;Pickett-Heaps et al, 1999) such as Spirogyra. Tannins are stored in vacuoles of this filamentous chlorophyte, comparable to higher plants.…”
Section: A Inhibition Of Enzymesmentioning
confidence: 99%
“…Most hydrolyzable polyphenols effectively complex proteins, and thus might inhibit enzymes (Haslam, 1989). The occurrence of hydrolyzable polyphenols in chlorophytes is limited to species belonging to the 'phragmoplast' group (see Sawitzky and Grolig, 1995;Pickett-Heaps et al, 1999) such as Spirogyra. Tannins are stored in vacuoles of this filamentous chlorophyte, comparable to higher plants.…”
Section: A Inhibition Of Enzymesmentioning
confidence: 99%
“…During cellularization of certain multinucleated plant cells, spindles do not precede phragmoplast assembly. However, here another bipolar microtubule array is reported to form between nuclear surfaces to act as a precursor for the phragmoplast (Van Lammeren et al 1985;reviewed in Otegui and Staehelin 2000;Pickett-heaps et al 1999;De Storme and Geelen 2013). Thus, in general, the phragmoplast maintains the bipolarity that is established by a preceding microtubule structure.…”
Section: Cell Plate Formationmentioning
confidence: 70%
“…However,insomemodernphylogeneticstudies,Co leo chae ta les and Zygnematales are also characterized as sister groupsof landplants.Ultrastructuralstudiesrevealedcelldi vi sion due to a type of phragmoplast in Zygnematales that broughtthemtogetherwithcharophytic(Charales)andCo leo chae tes (Coleochaetales) algae, as well as with ter rest ri al plants (Mattox & Stewart 1974, PickettHeaps 1975. The fol lowing biochemical and molecular studies have found that Zygnematophyceae is one of the advanced groups of Strep to phytealgae,althoughnooneof theobtainedto po lo gies has been supported statistically.…”
Section: Phylogenesis Of the сHarophytesmentioning
confidence: 99%
“…Equally important, but rather essential for the evolution of Charophyte multicellularity andthefor ma tionof threedimensionalbody of plants ge ne ral ly, was the phragmoplast, which is a special adaptation in the form of ve siclesandmic ro tu bulesformedduringcyto ki nesis (PickettHeaps 1975). This process of inte rac tionbet weencellswasfoundinZyg ne ma ta les, Coleochaetales, Charales, and ter rest rialplants(Marchant&PickettHeaps1973).It is assumed that the emergence of phragmoplast con tributedtotheformationof twoorthree di men sionalorganisms'aggregatesof cellsdu ring their division, with further development of the integrated plant's thallome (Hageman 1999,PickettHeapsetal.1999.…”
Section: Multicellularitymentioning
confidence: 99%